Quality improvement implications for health care professionals and managers - Guo, Kristina L. (International journal of quality health care assurance ;, 2004)
Voluntary organisations are an integral part of community care, and the available research indicates the value of their social support role. However, surprisingly little is known about the forms and functions of this support, or the links to the formal support provided by the National Health Service (NHS), so hampering quality improvements. Therefore, a small sample of voluntary service organisations in one English county participated in a pilot study. This involved the staff and users of these organisations, and a geographically linked sample of NHS mental health professionals. Interview data.